2022
DOI: 10.1007/s10608-022-10304-1
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Interplay Between Attention Bias and Interpretation Bias in Social Anxiety in Adolescents

Abstract: Background Cognitive biases are found to play a role in the onset and maintenance of social anxiety. However, particularly in adolescence, the link between different biases and their role in predicting social anxiety is far from clear. This study therefore investigated the interplay between attention bias and interpretation bias in relation to social anxiety in adolescence across three years. Methods 816 adolescents in grade 7 to 9 participated at three ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…We also expected negative AB to prospectively predict depression based on previous studies of adults (Beevers & Carver, 2003; Sanchez-Lopez et al, 2019; Yaroslavsky et al, 2019) and children (Cole et al, 2011; Hayden et al, 2014; Price et al, 2016). Given that parental depression also predicts offspring anxiety (Weissman et al, 2016) and IB have been found to prospectively predict symptoms of youth anxiety (Henricks et al, 2022), we explored the extent to which cognitive biases in children of depressed parents predicted the onset of anxiety symptoms. Finally, in line with diathesis-stress models of depression (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We also expected negative AB to prospectively predict depression based on previous studies of adults (Beevers & Carver, 2003; Sanchez-Lopez et al, 2019; Yaroslavsky et al, 2019) and children (Cole et al, 2011; Hayden et al, 2014; Price et al, 2016). Given that parental depression also predicts offspring anxiety (Weissman et al, 2016) and IB have been found to prospectively predict symptoms of youth anxiety (Henricks et al, 2022), we explored the extent to which cognitive biases in children of depressed parents predicted the onset of anxiety symptoms. Finally, in line with diathesis-stress models of depression (e.g.…”
Section: Introductionmentioning
confidence: 99%